Pag-ahon mula sa laylayan a Burkean analysis of the selected speeches of Philippine Vice President Maria Leonor Robredo - Madrid, Iris Kaye L.; De Luna, Teresa Paula S. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
This study anlyzes Philippine Vice President Maria Leonor Robredo's key speeches: her (1) Inaugural Speech, (2) International Women's Moth Speech, (3) Message for the 32nd Anniversary of EDSA Revolution, (4) Message during #Respeto Naman Nationwide Campaign against Gender-Based Violence, and her (5) Ahon Laylayan Koalisyon NCR Assembly and Covenant Signing speech through the lens of Burkean dramatism. The objective of the research is to determine the mnotives of Vice President Robredo based on an analysis of her selected speeches using the researcher's own qualitative observations with Burkean dramatism as a vantage point. The researcher made use of the elements of the dramatistic pentad which are the following: (1) Scene, (2) Act, (3) Agent, (4) Agency, (5) and Purpose.The researcher first read the speeches to identify the elements of Burke's pentad and then analyzed them using Agent-Act ratio. The researcher was able to form an idea of Robredo's motive and common patterns which could be found throughout her speeches as her constant mentioning her husband, her willingness to empower women, that she is an underdog in the current socio-political situation, and how she plays it safe with regard to her critics. Based on the researcher's pentadic analysis of the elements of Robredo's speeches, it ws determined that Vice President Leni Robredo's projected motives are the following: (1) She wants to unite the Filipino people, (2) She wants to uplift the image of the Liberal Party, and (3) She wants to empower women. The researcher concludes that while Robredo's motives may outwardly appear impersonal, the vice president has motives which can only be observed through a critical reading of her speeches.
Thesis (B.A. in Speech Communication)--University of the Philippines Diliman
Includes bibliographical references and appendices.